The Change of the American Dream Concept During Donald Trump's Presidency - Bouchenak, Assia; Aribi , Ibrahim (Faculty of Letters and Foreign Languages Department of English, 2018)
The study aims at exploring the concept of the American dream throughout history. The American dream became a little bit more complex than it once was. Besides, it aims at studying the transformation of the dream under the current United States President Donald Trump. His administration suggested executive reforms; it destroyed the dream of many. The research is an attempt to discover the effect of President Donald Trump administration on the dream. Also, the study demonstrates that President Donald Trump became the murder of the American dream.Nowadays, the dreamers’ destiny is in the hand of congress. The longer congress waits, the more dreamers will become a subject to immediate deportation